Multiplicity of Solutions for a Class of Fourth-Order Elliptic Problems with Asymptotically Linear Term - Qiong Liu; Dengfeng Lü (Journal of Applied Mathematics)
We study the following fourth-order elliptic equations: Δ2𝑢+𝑎Δ𝑢=𝑓(𝑥,𝑢),𝑥∈Ω,𝑢=Δ𝑢=0,𝑥∈𝜕Ω, where Ω⊂ℝ𝑁 is a bounded domain with smooth boundary 𝜕Ω and 𝑓(𝑥,𝑢) is asymptotically linear with respect to 𝑢 at infinity. Using an equivalent version of Cerami's condition and the symmetric mountain pass lemma, we obtain the existence of multiple solutions for the equations.